Handbook of the American Novel of the Twentieth and Twenty-First Centuries - Müller, Timo (Handbooks of English and American studies, 2017)
Increasing specialization within the discipline of English and American Studies has shifted the focus of scholarly discussion toward theoretical reflection and cultural contexts. These developments have benefitted the discipline in more ways than one, but they have also resulted in a certain neglect of close reading. As a result, students and researchers interested in such material are forced to turn to scholarship from the 1960s and 1970s, much of which relies on dated methodological and ideological presuppositions. The handbook aims to fill this gap by providing new readings of texts that figure prominently in the literature classroom and in scholarly debate − from James’s The Ambassadors to McCarthy’s The Road. These readings do not revert naively to a time “before theory.” Instead, they distil the insights of literary and cultural theory into concise introductions to the historical background, the themes, the formal strategies, and the reception of influential literary texts, and they do so in a jargon-free language accessible to readers on all levels of qualification